Peningkatan Proses Pembelajaran Tematik Terpadu dengan Menggunakan Model Discovery Learning di Kelas IV - Syaifulah, Nasri; Zuardi, Zuardi (Universitas Negeri Padang, 2022)
This study aims to explain student learning outcomes in integrated thematic learning using the Discovery Learning model in class IV SD Negeri 08 Pasar Surantih. This research is a classroom action research (PTK) using qualitative and quantitative approaches. The subjects of this study were class teachers as observers, researchers as practitioners, and 22 fourth grade students at SD Negeri 08 Pasar Surantih. The results of this study are: (1) The percentage of RPP assessments has increased from 80% in cycle I to 90% in cycle II. (2) In the teacher aspect, it increased from 81.25% in cycle I to 93.75% in cycle II. (3) In the student aspect, it increased from 81.25% in the first cycle to 93.75% in the second cycle.